Cystic Fibrosis and Genotype-Dependent Therapy: Is There a Need for a Sex-Specific Therapy?. (24th July 2020) - Bradbury, Neil A.
Cystic fibrosis (CF) is an autosomal recessive genetic disease caused by mutations in the cystic fibrosis transmembrane conductance regulation (CFTR) anion channel. Loss of CFTR protein and/or function disrupts chloride, bicarbonate, and fluid transport and also impacts epithelial sodium transport. Such altered ion and fluid transport produces mucus obstruction, inflammation, pulmonary infection, and damage to multiple organs. Although an autosomal disease, it is apparent that gender differences in life expectancy and quality of life do exist. Conventionally established therapies have treated the downstream sequelae of CFTR dysfunction and have led to a steady increase in life expectancy. Physicians now have access to medications that treat the basic defect in CF, in the form of CFTR modulators. These drugs target the trafficking and/or function of CFTR to improve clinical outcomes for patients. This review summarizes the science behind CFTR modulators and shows how these drugs have dramatically changed how patients with CF are treated. Surprisingly, although the drug target(s) are identical in males and females, CF females seem to display a greater improvement than their male counterparts.